NEW UZBEKISTAN - NEW NEIGHBORHOOD - Ismailova Ogiloy Sabir, (Galaxy International Interdisciplinary Research Journal, 2021)
The article of large-scale work , Movements strategy in all spheres, in accordance with the reforms implemented in Central Asia and neighboring countries with peace , stability, goodneighborly,friendly relations to explain.